Explosive outbreak of SARS-CoV-2 Omicron variant is associated with vertical transmission in high-rise residential buildings in Hong Kong. (1st August 2022) - Cheng, Vincent Chi-Chung; Wong, Shuk-Ching; Au, Albert Ka-Wing; Zhang, Cheng; Chen, Jonathan Hon-Kwan; So, Simon Yung-Chun; Li, Xin; Wang, Qun; Lu, Kelvin Keru; Lung, David Christopher; Chuang, Vivien Wai-Man; Schuldenfrei, Eric; et al.
Abstract: The phenomenon of vertical transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in high-rise residential buildings (HRRBs) is unique in our densely populated cosmopolitan city. The compulsory testing of a whole building under the scheme of restriction-testing declaration (RTD) during the fourth wave (non-Omicron variant) and fifth wave (mostly Omicron variant) of COVID-19 outbreak in Hong Kong allowed us to study the prevalence of this phenomenon, which may represent a form of airborne transmission. From 23 January 2021 to 24 March 2022, 25, 450 (5.8%) of 436, 397 residents from 223 (63.0%) of 354 HRRBs under RTD were test-positive for SARS-CoV-2. Using the clustering of cases among vertically aligned flats with shared drainage stack and lightwell as a surrogate marker of vertical transmission, the number of vertically aligned flats with positive COVID-19 cases was significantly higher in the fifth wave compared with the fourth wave (14.2%, 6471/45, 531 vs 0.24%, 3/1272; p < 0.001; or 2212 vs 1 per-million-flats; p < 0.001). Excluding 22, 801 residents from 38 HRRBs who were tested negative outside the 12-week periods selected in fourth and fifth waves, the positive rate among residents was significantly higher among residents during the fifth wave than the fourth wave (6.5%, 25, 434/389, 700 vs 0.07%, 16/23, 896; p < 0.001). Within the flats with COVID-19 cases, the proportion of vertically aligned flats was also significantly higher in the fifth wave than in the fourth wave (95.6%, 6471/6766 vs 30.0%, 3/10, p < 0.001). The proportion of HRRBs with COVID-19 cases was significantly higher during the corresponding 12-week period chosen for comparison (78.2%, 219/280 vs 11.1%, 4/36; p < 0.001). Whole-genome phylogenetic analysis of 332 viral genomes showed that Omicron BA.2 was the predominant strain, supporting the high transmissibility of BA.2 by airborne excreta-aerosol route in HRRBs of Hong Kong. Graphical abstract: Image 1 Highlights: Compulsory RT-PCR testing for COVID-19 was performed for residents. 5.8% of 436, 397 residents tested-positive for SARS-CoV-2. 63.0% of 354 high-rise residential buildings affected. Omicron BA.2 was the predominant strain. Vertical airborne transmission was hypothesized.